2015
DOI: 10.1016/j.yjmcc.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 regulates matrix gla protein and calcification gene networks in human valve endothelium

Abstract: Valvular and vascular calcification are common causes of cardiovascular morbidity and mortality. Developing effective treatments requires understanding the molecular underpinnings of these processes. Shear stress is thought to play a role in inhibiting calcification. Furthermore, NOTCH1 regulates vascular and valvular endothelium, and human mutations in NOTCH1 can cause calcific aortic valve disease. Here, we determined the genome-wide impact of altering shear stress and NOTCH signaling on aortic valve endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 43 publications
1
49
0
Order By: Relevance
“…Mutations in NOTCH1 have been linked with the presence of aortic valve calcification in human and mouse studies, although the disease was much milder in the latter . A recent study of NOTCH1 in human aortic VECs found that this factor positively regulated MGP . Shear stress was simulated by media flow conditions in vitro and was found to activate NOTCH1 expression .…”
Section: The Cardiovascular System Diseases and Insightsmentioning
confidence: 97%
“…Mutations in NOTCH1 have been linked with the presence of aortic valve calcification in human and mouse studies, although the disease was much milder in the latter . A recent study of NOTCH1 in human aortic VECs found that this factor positively regulated MGP . Shear stress was simulated by media flow conditions in vitro and was found to activate NOTCH1 expression .…”
Section: The Cardiovascular System Diseases and Insightsmentioning
confidence: 97%
“…Notch1 is essential in endothelial cells for proper development of the vasculature (32) and in the endocardium for endocardial cushion formation and ventricular trabeculation (41,42). Roles for endothelial Notch1 have also been described in adult cardiovascular disease, including valve calcification (43,44 Figure 2). Several publications have demonstrated a less predominant role for Notch1 in SMC in the vasculature, including neointimal repair after injury (46)(47)(48).…”
Section: ;Fbn1mentioning
confidence: 99%
“…Mechanistically, MGP deletion results in increased Notch signaling via enhanced expression of the Notch ligand Jagged1 [75] and accordingly, deletion of a single Jagged1 or Jagged2 allele in MGP knockout animals suppresses arteriovenous malformations [77]. Although it is not yet clear how MGP controls Jagged1 expression, it appears that MGP expression is also controlled by Notch in shear-stressed aortic valve endothelium, [78] suggesting that Notch and MGP are coordinated by a feedback regulation.…”
Section: Indirect Ecm-notch Interactions That Control Notch Signalingmentioning
confidence: 99%